A 1-D alternating copper(II) chain based on three acetate-bridging modes: synthesis, crystal structure, DNA binding and magnetic properties. Issue 14 (17th July 2016) - Zhao, Chun-Lai; Xie, Li-Fu; Li, Bing; Qiao, Xin; Xie, Cheng-Zhi; Bao, Wei-Guo; Xu, Jing-Yuan
Abstract: A new 1-D alternating copper(II) polymer, [Cu2 (L)(OAc)4 ]n (1 ) (L = 5-chloro-2-(pyridine-2-yl)benzo[ d ]thiazole), has been isolated and characterized by single-crystal X-ray diffraction, elemental analysis, IR spectroscopy, and magnetic susceptibility. The complex crystallized in the triclinic space group P-1, a = 8.2277(16) Å, b = 9.4233(19) Å, c = 15.831(3) Å, α = 103.38(3)°, β = 99.95(3)°, γ = 92.70(3)°, V = 1171.3(4) Å 3, and comprises a 1-D polymer linked by three kinds of acetate-bridging modes in an alternating manner. UV–visible and fluorescence spectra revealed that1 is bound to CT-DNA in a partial intercalation mode. Through gel electrophoresis assays, 1 displayed an efficient oxidative cleavage activity on supercoiled plasmid DNA (pUC19) in the presence of H2 O2 . Magnetic measurements were performed from 2 to 300 K, and the experimental results were satisfactorily reproduced with J 1 = –160 ± 20 cm −1, J 2 = 5.8 ± 0.2 cm −1, zJ′ = 0.381 ± 0.005 cm −1 and g = 2.1, showing antiferromagnetic coupling between Cu1 and Cu1i, ferromagnetic exchange between Cu2 and Cu2ii, and a weak ferromagnetic molecular field correction accounting for all interspecies interactions. Abstract :